Perlindungan Hukum Pemakaian Alat Perlindungan Diri Apron Untuk Pasien Pada Pemeriksaan Radiologis Panoramik - Ermiza, Linda (Jurnal JURISTIC, 2024)
The patient is a consumer whose rights must be legally protected, especially when it comes to the patient's health while undergoing examination and treatment at the hospital. In some cases the patient is examined by X-ray examination to diagnose a disease, one of which is a panoramic X-ray examination. Panoramic examination is a supporting examination used in dentistry in the form of X-rays. This oral and dental examination aims to see further and clearly describe the teeth and the surrounding soft tissue. Considering the losses caused by radiation exposure, there are many efforts made by the hospital to reduce and minimize exposure to radiation received. One of them is a policy in the use of Personal Protective Equipment in accordance with SOPS made by the government or the company itself. The radiation protection equipment according to PERKA BAPETEN No. 8 of 2011 paragraph 3 letter b, namely: Apron, Gonad Shield, Thyroid Shield, Pb Gloves, Pb Glasses, Pb Glass. This study uses a normative juridical approach regarding the legal protection of patients in the use of apron personal protective equipment during X-rays panoramic examinations with the main data source being secondary data supported by primary data. Primary data was obtained directly through the results of a questionnaire based on the results of a questionnaire checklist of 30 patients who came for treatment at the Oral Surgery Polyclinic at BENDAN Hospital in Pekalongan in the period December 2022 and had brought the results of panoramic examinations from various radiology laboratories whether they wore personal protective equipment before the examination or not.. From the results of the questionnaire on 30 patients who came to the mouth, it was obtained that most of the patients did not wear aprons. Legal protection for patients that underlies the use of apron personal protective equipment for radiological examinations as stipulated in Article 2 of Law no. 36 of 2009, namely Health Development is carried out on the basis of humanity, balance, benefits, protection, respect for rights and obligations, justice, gender and non-discrimination and religious norms.